Light pollution, sleep deprivation, and infant health at birth. (22nd December 2020) - Argys, Laura M.; Averett, Susan L.; Yang, Muzhe
Abstract: We conduct the first study to examine the fetal health impact of light pollution based on a direct measure of skyglow, an important aspect of light pollution. Using an empirical regularity discovered in physics (called Walker's law) as an instrumental variable, we address the potential endogeneity problem associated with the skyglow variable. We find evidence of reduced birth weight, shortened gestational length, and increases in preterm births. Specifically, increased nighttime brightness, characterized by being able to see only one‐fourth to one‐third of the stars that are visible in the natural unpolluted night sky, is associated with an increase of 1.48 percentage points in the likelihood of a preterm birth. Our study adds to the literature on the impact of early‐life exposure to pollution, which so far has focused primarily on air pollution. Our study has important policy implications regarding the necessity of minimizing skyglow that is, for example, contributed by streetlights.